Procompetitive gains from trade and comparative advantage - Albert G. Schweinberger (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
The concepts of comparative and "noncomparative" advantagegains/losses from trade are made precise, related to each other and to an aggregate measure of trade gains in a general equilibrium model with increasing returns to scale and imperfect competition (with any finite number of goods and factors). Making use of concepts of the theory of output rationing a novel necessary condition for trade gains is derived and interpreted. Subject to certain assumptions the theorems of comparative advantage for goods trade and the H-0 theorem in its factor content form are generalized to economies with increasing returns to scale and imperfect competition.
Keywords: 330